Challenge of Neurosurgical Practices during Covid-19 Pandemic - Haroon, Kaisar; Taher, Tania; Alam, Md Shafiul; Ahmed, Md Farhad (Bangladesh Journal of Infectious Diseases, 2020)
The COVID 19 pandemic has changed the world forever. As healthcare facilities were struggling to care for the infected patients, neurosurgeons had to postpone routine surgeries and continue with emergency procedures. They had to take unprecedented measures of protection. The safety and protective measures observed in the hospital for about five months were recorded. These measures were on effect all these time. COVID 19 is very contagious. The preventive and disinfection measures changed our way of consultation in OPD, admission in the wards and surgical and post-operative measures. This changed the practice in our institution. In this paper we look at how the pandemic had changed our practice of neurosurgery. Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S69-S71